Data Breach Aftermath and Recovery for Individuals and Institutions: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
In January 2016, the National Academies of Sciences, Engineering, and Medicine hosted the Workshop on Data Breach Aftermath and Recovery for Individuals and Institutions. Participants examined existing technical and policy remediations, and they discussed possible new mechanisms for better protecting and helping consumers in the wake of a breach. Speakers were asked to focus on data breach aftermath and recovery and to discuss ways to remediate harms from breaches. This publication summarizes the presentations and discussions from the workshop.
Keywords: Computers and Information Technology

Progress of Four Programs from the Comprehensive Addiction and Recovery Act - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Substance use disorder (SUD) and opioid use disorder are significant public health threats that affect millions of Americans each year. To help address overdose deaths and lack of access to treatment, the Comprehensive Addiction and Recovery Act (CARA) was signed into law on July 22, 2016. CARA is extensive legislation intended to address many facets of the opioid epidemic, including prevention, treatment, recovery, law enforcement, criminal justice reform, and overdose reversal. It authorizes more than $181 million each year in new funding to fight the opioid epidemic and it requires the implementation of programs and services across the United States to address SUD and recovery. Following the passage of CARA, the Departments of Education, Health and Human Services (HHS), and Labor, along with the 2018 Related Agencies Appropriations Act, included appropriations for a study of the Substance Abuse and Mental Health Services Administration (SAMHSA) components in CARA, to be conducted by the National Academies of Sciences, Engineering, and Medicine. In response to this charge, the National Academies formed an ad hoc committee to review outcomes achieved by four programs funded by SAMHSA through CARA: State Pilot Grant Program for Treatment for Pregnant and Postpartum Women (PPW-PLT), Building Communities of Recovery (BCOR), Improving Access to Overdose Treatment (OD Treatment Access), and First Responders (FR-CARA). The committee's review is designed to result in three reports over 5 years. This report, the second in the series, reviews reported outcomes and metrics to assess progress toward achieving program goals.
Keywords: Health and Medicine

Partnerships for Equitable Pandemic Response and Recovery - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The COVID-19 pandemic had a disproportionate impact on historically marginalized communities—including Black, Latino, and low-income individuals, as well as older adults, and people with chronic health conditions or disabilities. As transit agencies build toward recovery and rethink or reimagine their operations, they might consider grounding their decision-making in equity principles. The TRB Transit Cooperative Research Program's TCRP Synthesis 167: Partnerships for Equitable Pandemic Response and Recovery identifies how transit agencies were able to quickly pivot during the pandemic to deploy resources for other temporary “incidental uses” and respond to the need for essential services. Through these incidental uses of vehicles and facilities, public transit agencies across the country kept workers actively employed while expanding equitable access in unprecedented ways.
Keywords: Transportation and Infrastructure

Development of Clear Recovery Area Guidelines - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
The clear zone concept for roadside design emerged in the mid-1960s as a single distance for lateral clearance that reduced the likelihood of an errant vehicle striking a roadside obstacle. Subsequent recovery area guidance that evolved over the next two decades provided a variable distance expressed in terms of traffic volume, design speed, sideslope, and other roadway and roadside factors. NCHRP Research Report 1097: Development of Clear Recovery Area Guidelines, from TRB's National Cooperative Highway Research Program, develops updated guidelines for roadside clear zones expressed in terms of key roadway and roadside design parameters. These updated guidelines can aid designers in better understanding the risk associated with roadside encroachments while recognizing and working within the associated design constraints.
Keywords: Transportation and Infrastructure

Engineering for Pandemics: Preparedness, Response, and Recovery: Proceedings of a Forum - National Academy of Engineering (The National Academies Press, 2021)
The 2020 Annual Meeting of the National Academy of Engineering took place under the most unusual circumstances in the Academy's 56-year history. In January 2020 the first few cases of a respiratory illness caused by a newly identified coronavirus were reported in the United States. By March, COVID-19 had become a global pandemic. As soon as the first few cases were reported, engineers began working wiith scientists, medical professionals, and others in the public and private sector to address needs generated by the pandemic. They brought automation, process control, and artificial intelligence to the production of protective equipment, diagnostics, and therapeutics. They established robust supply chains of critical materials. They strengthened the communication technologies and platforms that allowed people to telework and keep in touch with friends and family members. The 2020 annual meeting was held virtually. The two main plenary presentations, delivered by David Walt, the Hansjörg Wyss Professor of Biologically Inspired Engineering at Harvard Medical School, and Pam Cheng, executive vice president of global operations and information technology for AstraZeneca, focused on the critical role of engineers in responding to the epidemic. Similarly, the annual forum, held the next day and organized by NAE executive officer Al Romig, Jr., and a distinguished organizing committee, was entitled "Engineering for Pandemics: Preparedness, Response, and Recovery". The plenary and forum presentations, which are summarized in this volume, abundantly demonstrate the essential functions that engineers have performed in responding to the virus. They also reveal the lessons derived from engineering that must be absorbed to prepare effectively for future pandemics and for other disasters, expected and unexpected, that will certainly occur in the future.
Keywords: Engineering and Technology

Review of the Inland Estimated Recovery System Potential (ERSP) Prototype Calculator - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
In the wake of major oil spills, including the Exxon Valdez spill in 1989 and Deepwater Horizon spill in 2010, the United States developed tools for calculating the clean-up capability of oil spill response equipment. These tools, while useful for open-water spills, had limited applicability in nearshore and inland environments, leading the U.S. Coast Guard and partners to develop a new, inland Estimated Recovery System Potential (ERSP) calculator for oil recovery. The present review evaluates the inland ERSP calculator and accompanying documentation. While acknowledging the complexities associated with developing such a calculator for inland environments, the report recommends changes to the methodologies used and the software developed to better meet user needs. The calculator should be modified to more clearly establish the scope of its capabilities, so users understand the limitations on data they can input as well as what the calculator outputs tell them about the recovery potential of selected clean-up equipment. The calculator should also undergo thorough third-party validation and verification as well as quality assurance testing, to ensure it operates as intended.
Keywords: Earth Sciences

Frontiers in Massive Data Analysis - National Research Council (The National Academies Press, 2013)
Data mining of massive data sets is transforming the way we think about crisis response, marketing, entertainment, cybersecurity and national intelligence. Collections of documents, images, videos, and networks are being thought of not merely as bit strings to be stored, indexed, and retrieved, but as potential sources of discovery and knowledge, requiring sophisticated analysis techniques that go far beyond classical indexing and keyword counting, aiming to find relational and semantic interpretations of the phenomena underlying the data. Frontiers in Massive Data Analysis examines the frontier of analyzing massive amounts of data, whether in a static database or streaming through a system. Data at that scale—terabytes and petabytes—is increasingly common in science (e.g., particle physics, remote sensing, genomics), Internet commerce, business analytics, national security, communications, and elsewhere. The tools that work to infer knowledge from data at smaller scales do not necessarily work, or work well, at such massive scale. New tools, skills, and approaches are necessary, and this report identifies many of them, plus promising research directions to explore. Frontiers in Massive Data Analysis discusses pitfalls in trying to infer knowledge from massive data, and it characterizes seven major classes of computation that are common in the analysis of massive data. Overall, this report illustrates the cross-disciplinary knowledge—from computer science, statistics, machine learning, and application disciplines—that must be brought to bear to make useful inferences from massive data.
Keywords: Math, Chemistry, and Physics; Surveys and Statistics

Using Syndemic Theory and the Societal Lens to Inform Resilient Recovery from COVID-19: Toward a Post-Pandemic World: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
On March 17, 2021, the Forum on Microbial Threats of the National Academies of Sciences, Engineering, and Medicine's Health and Medicine Division hosted a virtual workshop on considering COVID-19 through a syndemic approach (analyzing the health consequences and interactions of multiple epidemics within a population in combination with underlying social, environmental, and economic drivers) and the implications that perspective might have for the ongoing response efforts in the United States and around the world. In addition, the meeting sought to raise prospective ideas for enhancing resilience and preparedness for future outbreaks. This event kicked off the forum's initiative to evaluate lessons learned from the pandemic and served as a framing workshop for thinking about its long-term, cross-sectoral, and global impacts. Speakers and panelists addressed (1) the biological and social determinants of health that are involved in identifying and describing syndemics; (2) the reasons for and implications of using the syndemic framing for COVID-19, based on the influence of particular geographic and community contexts on localized disease impacts; and (3) why thinking about COVID-19 and other disease outbreaks through a syndemic lens is important for public health officials and the general public. This Proceedings of a Workshop-in Brief summarizes the presentations and discussions that occurred at the workshop. A broad range of perspectives were shared during the event.
Keywords: Health and Medicine

Statistical Analysis of Massive Data Streams: Proceedings of a Workshop - National Research Council (The National Academies Press, 2004)
Massive data streams, large quantities of data that arrive continuously, are becoming increasingly commonplace in many areas of science and technology. Consequently development of analytical methods for such streams is of growing importance. To address this issue, the National Security Agency asked the NRC to hold a workshop to explore methods for analysis of streams of data so as to stimulate progress in the field. This report presents the results of that workshop. It provides presentations that focused on five different research areas where massive data streams are present: atmospheric and meteorological data; high-energy physics; integrated data systems; network traffic; and mining commercial data streams. The goals of the report are to improve communication among researchers in the field and to increase relevant statistical science activity.
Keywords: Computers and Information Technology; Math, Chemistry, and Physics; Surveys and Statistics

Massive Data Sets: Proceedings of a Workshop - National Research Council (The National Academies Press, 1996)
Keywords: Math, Chemistry, and Physics; Computers and Information Technology; Surveys and Statistics

Expediting Aircraft Recovery at Airports - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2012)
TRB’s Airport Cooperative Research Program (ACRP) Synthesis 38: Expediting Aircraft Recovery at Airports includes suggested procedures to help airports expedite the recovery of disabled aircraft that are designed to avoid injury to personnel, damage to airport equipment, and secondary damage to the aircraft.For the purposes of the report, a disable aircraft is defined as on that is unable to move using its power after an excursion from a runway or taxiway.
Keywords: Transportation and Infrastructure

Bridge Element Data Collection and Use - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Initial efforts to define and collect bridge element data in the United States started in the late 1990s with the development and implementation of bridge management systems (BMSs). Over the years, the bridge management community provided feedback and made suggestions to improve the bridge element inspection methodology.The TRB National Cooperative Highway Research Program's NCHRP Synthesis 585: Bridge Element Data Collection and Use documents current state departments of transportation (DOTs) practices and experiences regarding collecting element-level data and ensuring data accuracy. The synthesis also examines how state DOTs are using the data from inspection reports.
Keywords: Transportation and Infrastructure

Toward a New Era of Data Sharing: Summary of the US-UK Scientific Forum on Researcher Access to Data - National Academy of Sciences (The National Academies Press, 2024)
Data are at the forefront of efforts to solve many of today's greatest problems, including climate change, misinformation and disinformation, the threat of future global pandemics, and the quest by people everywhere to lead better lives. But if researchers are going to use data to contribute to the solutions of problems, data need to be available for them to use. Over time, data have become increasingly voluminous, complex, and heterogeneous. Massive volumes of data are being generated by new devices and methods, and many of these data are not easy to analyze, interpret, or share. Groups that generate data may be reluctant to share them for a variety of professional, personal, financial, regulatory, and statutory reasons.These issues were addressed during the US-UK Scientific Forum on Researcher Access to Data held in Washington, DC, on September 12–13, 2023. Organized by the National Academy of Sciences and the Royal Society, the forum examined the constellation of issues surrounding researchers' access to data, best practices and lessons learned from exemplary research disciplines, and new ideas and techniques that could drive research forward. This publication summarizes the presentations and discussions of the forum.
Keywords: Policy for Science and Technology

LTPP Data Analysis: Practical Tools and Procedures to Improve WIM Data Quality - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Highway agencies use weigh-in-motion (WIM) technology to collect vehicle weight and axle load data on roadways. NCHRP Web-Only Document 370: LTPP Data Analysis: Practical Tools and Procedures to Improve WIM Data Quality, from TRB's National Cooperative Highway Research Program, is a supplemental document to NCHRP Research Report 1070: Tools for Assuring WIM Data Quality: Practical Guide, and provides a research overview and data analyses to enhance understanding of different factors affecting WIM measurement accuracy and to develop practical tools and procedures to improve accuracy and increase the reliability of WIM data. The document describes the development and use of to develop practical tools and procedures aimed to improve the accuracy and increase the reliability of WIM data. Supplemental to the document are four presentations.
Keywords: Transportation and Infrastructure

Airport Landside Data: Collection and Application (The National Academies Press, 2023)
Airports collect data to help understand the customer journey from the entrance or access points of the airport to the boarding gates. Processes may change in order to improve the customer experience when the collected data are analyzed. ACRP Synthesis 132: Airport Landside Data: Collection and Application, from TRB's Airport Cooperative Research Program, documents landside data, collection methods, analysis, and interpretation and discusses how that information affects airport decision-making.
Keywords: Transportation and Infrastructure

Legal Implications of Data Collection at Airports - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
As technology evolves, airports and their partners collect more data from passengers, employees, tenants, concessionaires, airlines, and others. This data is used in many ways, including for facility management, security, ground transportation, marketing, understanding passenger preferences, and enhancing the travel experience.The TRB Airport Cooperative Research Program's ACRP Legal Research Digest 42: Legal Implications of Data Collection at Airports provides a survey of applicable law; considerations for the collection and safekeeping of data; and a review of the issues that arise related to data collection among airports, their tenants, and other users. It also offers an understanding of the expansion in law around data collection and use.
Keywords: Transportation and Infrastructure

Use of Probe Data for Freight Planning and Operations (The National Academies Press, 2023)
As freight transportation volumes have grown rapidly—further spurred by pandemic-driven e-commerce growth—state departments of transportation (DOTs) have become increasingly reliant on probe data to monitor freight infrastructure performance, manage demand, and understand freight infrastructure needs. NCHRP Synthesis 611: Use of Probe Data for Freight Planning and Operations, from TRB's National Cooperative Highway Research Program, documents current state DOT practices regarding the use of probe data in freight planning and operations management applications to close this gap in understanding.
Keywords: Transportation and Infrastructure

Measuring Recovery from Substance Use or Mental Disorders: Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
In February 2016, the National Academies of Sciences, Engineering, and Medicine held a workshop to explore options for expanding the Substance Abuse and Mental Health Services Administration's (SAMHSA) behavioral health data collections to include measures of recovery from substance use and mental disorder. Participants discussed options for collecting data and producing estimates of recovery from substance use and mental disorders, including available measures and associated possible data collection mechanisms. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Behavioral and Social Sciences; Surveys and Statistics

Review of the Everglades Aquifer Storage and Recovery Regional Study - National Research Council (The National Academies Press, 2015)
The Florida Everglades is a large and diverse aquatic ecosystem that has been greatly altered over the past century by an extensive water control infrastructure designed to increase agricultural and urban economic productivity. The Comprehensive Everglades Restoration Plan (CERP), launched in 2000, is a joint effort led by the state and federal government to reverse the decline of the ecosystem. Increasing water storage is a critical component of the restoration, and the CERP included projects that would drill over 330 aquifer storage and recovery (ASR) wells to store up to 1.65 billion gallons per day in porous and permeable units in the aquifer system during wet periods for recovery during seasonal or longer-term dry periods. To address uncertainties regarding regional effects of large-scale ASR implementation in the Everglades, the U.S. Army Corps of Engineers (USACE) and the South Florida Water Management District conducted an 11-year ASR Regional Study, with focus on the hydrogeology of the Floridan aquifer system, water quality changes during aquifer storage, possible ecological risks posed by recovered water, and the regional capacity for ASR implementation. At the request of the USACE, Review of the Everglades Aquifer Storage and Recovery Regional Study reviews the ASR Regional Study Technical Data Report and assesses progress in reducing uncertainties related to full-scale CERP ASR implementation. This report considers the validity of the data collection and interpretation methods; integration of studies; evaluation of scaling from pilot-to regional-scale application of ASR; and the adequacy and reliability of the study as a basis for future applications of ASR.
Keywords: Earth Sciences

Uses of Social Media to Inform Operational Response and Recovery During an Airport Emergency - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
TRB's Airport Cooperative Research Program (ACRP) Synthesis 82: Uses of Social Media to Inform Operational Response and Recovery During an Airport Emergency summarizes airport practices and tools used by airport emergency managers. Using social media for emergency management, airports glean information and intelligence from the stream of posts and messages passing through social media and then apply this information to enhance situational awareness and resource allocation decisions by emergency managers. Such uses raise the stakes for timeliness of data extraction and validation of the results, especially if the information is going to be used for resource allocation and other decision making.
Keywords: Transportation and Infrastructure